Ilse Aichingers Verhältnis zur Gruppe 47 im Kontext der Shoah - Thomas Pekar (Studia austriaca)
Ilse Aichinger, whose debut novel Die größere Hoffnung was published in 1948 and is regarded as a work of Holocaust literature, only revisited the subject of the Shoah explicitly later in life. Why did she do so? This essay interprets the explicit receding of her memories of the Shoah in the context of the anti-Semitism prevalent in Group 47, of which Aichinger was a member after the war. Being part of that group required Aichinger to devise specific poetic strategies to maintain her voice and literary identity within this milieu.